Comparative Study of PDA Ligation in the OR versus in the NICU: A 10-Year Retrospective Cohort Study - Poopong, Kittipatr; Tantiwongkosri, Kriangkrai (Siriraj Medical Journal, 2024)
Objective: This study aimed to compare the outcomes of PDA (patent ductus arteriosus) ligation performed in NICU (neonatal intensive care unit) versus OR (operating room) and identify relevant influencing factors. Materials and Methods: In this retrospective review, spanning a decade (2012-2021) of NICU patients at Siriraj Hospital who underwent PDA ligation, patients were categorized into two groups: OR and NICU. Baseline clinical characteristics, operative details, and postoperative results (including hospital mortality, cause of death, and complications) were collected and analyzed. Results: A total of 118 patients were included, with 52 patients in the OR group and 66 patients in the NICU group. There were no statistically significant differences in postoperative outcomes between the two groups. The hospital mortality rates were 1.9% (1/52) and 10.6% (7/66), respectively (p = 0.08). Post hoc multivariable binary logistic regression analysis further confirmed that the location of PDA ligation was not associated with hospital mortality. However, higher oxygen requirements and lower postmenstrual age (PMA) were found to be independently associated with hospital mortality (OR 1.10, p =0.02 and OR 0.82, p<0.01 respectively). Hypothermia, defined as a body temperature less than 36C, was more prevalent in the OR group (30.8% vs 16.7%, p=0.07). Other postoperative complications were not statistically different between the two groups. Lastly, no case of surgical site infection was observed in the NICU group. Conclusion: PDA ligation can be safely and effectively performed in the NICU with comparable hospital mortality, potentially offering better temperature control, and without an increased risk of complications, including surgical site infection.